Ethnobotany, Ethnopharmacology and Drug Discovery: Ethnobotany and ethnopharmacology - Ghorbani, Abdolbaset; Naghibi, Farzaneh; Mosaddegh, Mahmoud (Iranian Journal of Pharmaceutical Sciences, 2006)
This manuscript is a review of a number of ethnobotany and ethnopharmacology texts and papers in order to arrive at current understanding and scope of ethnobotany and ethnopharmacology. It includes either a brief definition of both fields and presenting some examples on them. Also it has a glimpse on the geographical coverage of research works throughout the world, important issue of property rights and state of these fields in Iran.